New records of benthic marine macroalgae from the Caribbean coast of Costa Rica - Vega-Álvarez, Greivin (2018)
Abstract: Marine macroalgae are highly diverse and play an important role in marine ecosystems, influencing ecological processes. Recording the algae diversity with precise taxonomic identification is required to understand the marine ecosystems. The biodiversity of macroalgae along the southern Caribbean coast of Costa Rica has been studied by several authors, and the updated checklist includes 396 species of benthic marine algae reported for both Pacific and Caribbean coasts of Costa Rica, from which 287 are recorded from the Caribbean. Eighty percent of the total specimens from the Caribbean coast deposited in botanical collections in Costa Rica were collected at Cahuita National Park, an area where most of the studies have been carried out. This study reports on the addition of five new species and one genus of marine benthic macroalgae to the Caribbean Costa Rican flora, found at the poorly studied reefs of Playa Chiquita (Punta Cocles) and Punta Uva. Sampling was directed, searching for benthic macroalgae at Chiquita beach (SCUBA diving and snorkel) and Punta Uva (snorkel only), during October 2014. Specimens were deposited in the Dr. Luis A. Fournier Origgi Herbarium of the University of Costa Rica (USJ). Most of the new records were Chlorophyta, followed by Rhodophyta and Ochrophyta-Phaeophyceae. We recorded four new genera for the Caribbean coast of Costa Rica: Microdictyon Decaisne, 1841, Rhipidosiphon Montagne, 1842, Predaea G. De Toni, 1936, and Augophyllum S.-M. Lin, S. Fredericq & M. H. Hommersand, 2003. In conclusion, is necessary to continue the detailed taxonomic works in the Caribbean coast, focusing on areas poorly studied, in order to improve our knowledge of the marine flora of Costa Rica. Rev. Biol. Trop. 66(Suppl. 1): S328-S339. Epub 2018 April 01.